Analisis Pengaruh Produk Ramah Lingkungan Terhadap Nilai Pelanggan di Kota Pontianakâ€ (Studi Empiris pada Pelanggan Produk-Produk Elektronik Hemat Energi Di Kota Pontianak) - B11108042, SRI FATMAWATI (Jurnal Manajemen Update, 2015)
Several studies have shown that the value perceived by the customer has a positive effect on re-purchase intention, perception of value is considered as the best variable to predict the intention to buy again than veriabel satisfaction because of the perception of the value of a comprehensive assessment of the benefits received from product or services depends on the assessment of the benefits (gains) and losses (lost) and interpreted as a perception of value. Therefore, the value of the customer (customer value) is important to be considered by the company because it can explain the behavior of customers in choosing; that is why customers choose to buy or not buy a particular product or service. The purpose of this study was to determine the effect of philips lighting products to customer value in Pontianak, the research variables in this study are the buyer philips lighting products located in Pontianak. In this study the sample taken is non-probability sampling with accidental sampling technique, which is a technique based on the determination of a coincidence to meet with researchers can be used as a sample of 100 people. This research is an explanation of the methods of descriptive statistical analysis. This is a form of research through questionnaires. Regression results show that the variable lighting products philips positive and significant impact on customer value. That is, the more positive respondents to the product the customer value, the higher the value perceived by the customer either related to functional value, social value and emotional value. Keywords: Product, Customer Value.